Efficacy of therapeutic interventions for idiopathic recurrent pregnancy loss: a systematic review and network meta-analysis - Jorge Lima; Jorge Lima; João Guerreiro; Miguel Ângelo-Dias; Sofia Silvério Serra; Teresa Costa; Natália Marto; João Feldman de Pinho; João Costa; Rodrigo Ruano; Gonçalo Silva Duarte; Gonçalo Silva Duarte (Frontiers in Medicine)
BackgroundApproximately 50% of cases of recurrent pregnancy loss (RPL) remain unexplained, and there is a lack of consensus concerning the effective treatments for idiopathic RPL. We used network meta-analyses to evaluate the efficacy of several prophylactic therapeutic interventions used in women with idiopathic RPL.Materials and methodsWe conducted a systematic literature search using several databases from their inceptions to 20 July 2023. References from key articles were also manually searched. Randomized controlled trials assessing the efficacy and safety of any prophylactic intervention that were conducted in adult women with RPL were included. Studies with known causes of RPL were excluded. Two reviewers independently extracted data and assessed the risk of bias. Primary outcomes were live births and miscarriage rates. Secondary outcomes included serious adverse/adverse events and trial discontinuation. The network meta-analyses used a Bayesian hierarchical model with direct and indirect comparisons. Rank probabilities (assessed by surface under the cumulative ranking curve [SUCRA]) and certainty of evidence (assessed by Grading Recommendations Assessment, Development, and Evaluation [GRADE]) were also assessed.ResultsThirty-eight studies (6,379 participants) were evaluated. No statistically significant differences in live birth rates among the interventions were found. The three best-ranked interventions for this outcome were prednisone plus progesterone plus aspirin (83%), leukocyte immune therapy (74%), and prednisolone (65%). Women who were treated with progesterone plus human chorionic gonadotrophin (instead of a placebo) presented an increase in miscarriage odds (odds ratio [OR] 3.83, 95% credible intervals [CrIs] 1.04–14.38). The three best-ranked interventions for miscarriage rate were prednisone plus progesterone plus aspirin (SUCRA = 81%), hydroxychloroquine (SUCRA = 79%), and intralipid (SUCRA = 65%). Overall, under placebo, 59% (95% confidence interval [CI] 51–67; I2 = 92%) of participants underwent successful live births, and 35% (95% CI 30–42, I2 = 86%) underwent miscarriages. We found no evidence of statistically significant differences between interventions (the top three interventions were low-molecular-weight heparin, granulocyte colony-stimulating factor, and leukocyte immune therapy) in those who discontinued trial participation.ConclusionOur results suggest that none of the analyzed interventions led to improvements in the live birth rate or a reduction in the miscarriage rate in women with idiopathic RPL.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42023455668.